Utilization of Creative Dance Videos Via Youtube as an Innovative Cultural Arts Learning Media in Elementary Schools: Teachers’ Perspectives - Pamela Mikaresti; Agus Tatang Sopandi; Herlinda Mansyur; Elizar Elizar; Edy Susanto (Journal of Social Work and Science Education, 2026)
This study aims to explore the effectiveness of utilizing creative Indonesian traditional dance videos via YouTube as an innovative learning medium in cultural arts education in elementary schools. In addition, it highlights the contribution of audiovisual media in enhancing students’ interest, motivation, and engagement, while also supporting cultural preservation efforts. The research adopts a qualitative approach with Robert K. Yin’s (2009) case study design and employs a descriptive method. Data were collected through two stages of questionnaire surveys (136 teachers in the first stage and 124 teachers in the second stage), in-depth interviews with 18 teachers and prospective teachers selected purposively, and triangulation through thematic analysis, word cloud, and member checking. Strategic analysis was conducted using IFE, EFE, SWOT, and SPACE matrices to formulate strategies for implementing creative dance videos as learning media. The findings reveal that conventional dance learning using printed textbooks resulted in low levels of teacher and student interest and engagement. In contrast, the use of creative dance videos (Kedun Dance, Gegelea Beregam Dance, and Tatagok Dance) significantly increased teacher interest (99.8% interested/very interested), student motivation and engagement (73.4% more active), learning effectiveness (100% reported effective), and teacher creativity (91.9%). The novelty of this research lies in combining a qualitative case study approach with strategic analysis (SWOT and SPACE) to evaluate the use of digital media in cultural arts education. Its main contribution is offering a model for utilizing creative dance videos on YouTube as an innovative tool to enhance the quality of dance learning while strengthening Indonesia’s cultural identity among younger generations.